Enhancing the Efficacy and Safety of Methotrexate Treatment: A Focus on Drug Interactions (Review) - S. A. Doktorova; Yu. Yu. Grabovetskaya; M. Stefanov; V. V. Rafalskiy (Безопасность и риск фармакотерапии)
INTRODUCTION. Methotrexate (MTX) is the main disease-modifying antirheumatic drug (DMARD) and the gold standard for the safety and efficacy evaluation of biologicals and targeted small molecules. However, its narrow therapeutic range, interpatient variability in pharmacokinetics and pharmacodynamics, and potential clinically relevant drug–drug interactions (DDIs) may lead to treatment failure and increase the risk of adverse drug reactions (ADRs).AIM. The study aimed to describe the main clinically significant DDIs associated with MTX used in rheumatic disease therapy and determine possible approaches to addressing this issue based on a literature review.DISCUSSION. MTX is characterised by pharmacokinetic DDIs during absorption, cell penetration, and elimination. Some non-steroidal anti-inflammatory drugs (NSAIDs), theophylline, sulfasalazine, antibacterial agents, and proton pump inhibitors (PPIs) affect MTX elimination and therapeutic effects. The main ADRs associated with MTX include haematotoxicity, hepatotoxicity, lung tissue damage (interstitial pneumonitis and pulmonary fibrosis), and renal dysfunction. The severity of these ADRs depends on the dose, comorbidities, and concomitant therapy. The toxicity of MTX may be increased by the concomitant administration of medicinal products that exhibit haematotoxicity and affect renal function (impair the elimination of medicines). When co-administering MTX and medicines having clinically significant DDIs described in the literature, healthcare providers should consider the risk factors for each individual patient. The most significant risk factors include moderate to severe renal and hepatic impairment, older age, polypharmacy, and hypoalbuminemia.CONCLUSIONS. This article describes potential clinically significant interactions between MTX and certain NSAIDs, antibacterial agents, and PPIs that depend on individual patient characteristics and may increase the toxicity or decrease the effectiveness of MTX. MTX deprescribing, short-term withdrawal, and dosing optimisation may be considered as approaches to DDI risk mitigation.